Hubungan Bermain Tenis Meja pada Komunitas Olahraga Lokal terhadap Tingkat Stres dan Kebugaran Kardiovaskular pada Pekerja Karyawan di PTM VGH Bekasi - Novan Eka Ardhani; Moch Fahmi Abdulaziz (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
The purpose of this study was to determine the relationship between participation in table tennis and employees’ work stress levels and cardiovascular fitness. The method of this study was quantitative research with a correlational design. The sample consisted of 30 respondents selected using a purposive sampling technique. Data on participation in table tennis were collected using a four-point Likert scale questionnaire, work stress levels were measured using the stress subscale of the DASS-21, and cardiovascular fitness was measured using the Harvard Step Test. Data were analyzed using descriptive statistics and the Pearson Product-Moment correlation test at a significance level of 0.05. The results showed that the level of participation in table tennis was in the very high category with an index of 80%, while the level of work stress was in the moderate category with an index of 50%. The correlation test showed a significant negative relationship between participation in table tennis and work stress (r = -0.48; p < 0.05), as well as a significant positive relationship between participation in table tennis and cardiovascular fitness (r = 0.62; p < 0.05). In conclusion, participation in table tennis has a significant relationship with reducing work stress levels and improving employees’ cardiovascular fitness. Keywords: DASS-21, Harvard Step Test, Cardiovascular Fitness, Work Stress, Table Tennis